Transition Metal‐Catalyzed C−H Activation/Annulation Approaches to Isoindolo[2, 1‐b]isoquinolin‐5(7H)‐ones. Issue 3 (16th January 2023) - Tang, Xiao; Ding, Songtao; Song, Liangliang; Van der Eycken., Erik V.
Abstract: The isoindolo[2, 1‐ b ]isoquinolin‐5(7 H )‐one scaffold is widely present in lots of bioactive natural products. Diverse types of strategies have been developed to construct this scaffold. Recently, transition metal‐catalyzed C−H activation/annulation is emerging as a powerful and straightforward method to construct diverse polyheterocycles with high atom‐ and step‐economy. It also has been employed for the synthesis of the isoindolo[2, 1‐ b ]isoquinolin‐5(7 H )‐one scaffold. This review provides an introduction to recent advances for the preparation of isoindolo[2, 1‐ b ]isoquinolin‐5(7 H )‐ones by using transition metal‐catalyzed C−H activation/annulation. It will help researchers to find hidden opportunities and accelerate the discovery of novel transformations based on C−H activation/annulation. Abstract : This review describes the recent development to access isoindolo[2, 1‐ b ]isoquinolin‐5(7 H )‐ones through transition metal‐catalyzed C−H activation/annulation. By using various transition metals such as Rh, Ir, Pd and Ru, structurally diverse isoindolo[2, 1‐ b ]isoquinolin‐5(7 H )‐one scaffolds are obtained through an intermolecular or intramolecular pathway.